Impact of black carbon exposure on length of hospital stay in asthma patients: a retrospective cohort study in yulin, China - Yu Chen; Qian Huang; Huimeng Liu; Baosen Meng; Can Zhang; Xiaohui Li; Chunlai Yang; Mengchun Wang; Peiying Yang; Li Cheng; Baibing Mi; Yu Zheng (BMC Public Health)
Abstract Objective Background While PM₂.₅ exposure is linked to asthma exacerbations, components-specific effects on healthcare burden remain understudied. Hospital length of stay (LOS), a critical indicator of disease severity and healthcare costs, has received limited attention in black carbon (BC) research. Objective To quantify the association between short-term exposure to PM₂.₅ components-particularly black carbon (BC)-and LOS among asthma patients, and to identify vulnerable populations and critical exposure windows. Methods We conducted a retrospective cohort study of 4,509 asthma patients (ICD-10: J45 ~ J46) hospitalized in Yulin, China (2018 ~ 2023). Daily PM2.5 components concentrations (BC, Organic Matter, Sulfates, Nitrates, Ammonium) were derived from 10-km resolution CMAQ model data. General linear models (GLM) and restricted cubic spline (RCS) assessed exposure-response relationships across lag0-lag10, stratified by age groups and seasons. Confounders included meteorological variables, patient demographics, and clinical characteristics. Results Each 1.00 µg/m³ increase in BC concentration at lag9 significantly associated with a 0.45-days prolongation in hospital stay (95%CI: 0.12 ~ 0.78). Age-stratified analysis revealed heightened vulnerability in children (effect observed at lag1 ~ 3, lag7 ~ 9) and middle-aged adults (sustained effects lag2 ~ 10), while elderly patients showed no significant associations. Seasonal analysis demonstrated that BC effects were more pronounced during non-pollen season (0.77 additional days per 1.00 µg/m³ increase), with no significant effects during pollen season. Restricted cubic spline analysis confirmed dose-response relationships, with effects plateauing at BC concentrations ≥ 1.98 µg/m³. Conclusions Short-term BC exposure was significantly associated with extend asthma hospitalization duration, with critical exposure windows at lag9 and pronounced vulnerability in children and middle-aged adults during non-pollen seasons. These findings provide quantitative evidence supporting BC-specific emission controls in air quality policies and highlight the need for targeted protection of vulnerable populations, particularly in high-population regions.